To Assess the Lung Function Status by Measuring Peak Expiratory Flow of the Goldsmiths Working in Chennai Central: A Cross-Sectional Study - Gowri Velayutham; Sathya Palaniswamy; Parimala. A (International Journal of Science and Healthcare Research, 2026)
Background: Goldsmiths may be occupationally exposed to metal dust, fumes, and other airborne contaminants generated during jewellery manufacturing. Prolonged exposure to such occupational hazards may adversely affect respiratory function. This study assessed selected pulmonary function parameters among goldsmiths and compared them with jewellery shop workers who were not occupationally exposed to dust. Methods: A cross-sectional comparative study was conducted among 200 participants, comprising 100 goldsmiths and 100 jewellery shop workers. Goldsmiths aged 20–50 years who had worked for approximately 10 hours per day for at least 5 years were included. Age-matched, healthy jewellery shop workers without occupational dust exposure served as controls. Individuals with respiratory infections, tuberculosis, cardiovascular disease, diabetes, hypertension, previous chest or abdominal surgery, neuromuscular disorders, spinal abnormalities, other systemic illnesses, or a history of smoking were excluded. Pulmonary function testing was performed in the morning in the sitting position using an Easy One™ diagnostic spirometer. Peak expiratory flow (PEF), forced expiratory flow at 25–75% of forced vital capacity (FEF25–75%), and maximum voluntary ventilation (MVV) were assessed. Continuous variables were summarized as mean ± standard deviation and compared using Welch’s independent-samples t-test. A p-value